Numerical study of the melting of nano-enhanced phase change material in a square cavity - Sebti, Seyed Sahand; Mastiani, Mohammad; Mirzaei, Hooshyar; Dadvand, Abdolrahman; Kashani, Sina; Hosseini, Seyed Amir (Journal of Zhejiang University. A. Science, 2013)
A comprehensive numerical study was conducted to investigate heat transfer enhancement during the melting process in a 2D square cavity through dispersion of nanoparticles. A paraffin-based nanofluid containing various volume fractions of Cu was applied. The governing equations were solved on a non-uniform mesh using a pressure-based finite volume method with an enthalpy porosity technique to trace the solid-liquid interface. The effects of nanoparticle dispersion in a pure fluid and of some significant parameters, namely nanoparticle volume fraction, cavity size and hot wall temperature, on the fluid flow, heat transfer features and melting time were studied. The results are presented in terms of temperature and velocity profiles, streamlines, iso- therms, moving interface position, solid fraction and dimensionless heat flux. The suspended nanoparticles caused an increase in thermal conductivity of nano-enhanced phase change material （NEPCM） compared to conventional PCM, resulting in heat transfer enhancement and a higher melting rate. In addition, the nanofluid heat transfer rate increased and the melting time de- creased as the volume fraction ofnanoparticles increased. The higher temperature difference between the melting temperature and the hot wall temperature expedited the melting process of NEPCM.